A PRAGMATIC APPROACH TO COVID-19: A COMPREHENSIVE REVIEW OF THERAPEUTIC AND PREVENTIVE STRATEGIES - Mahalakshmi S; Vijay Krishnan; Harish Kumar B; Nirmala B; Athirayan S (The Bioscan, 2025)
The outbreak of the novel coronavirus disease (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has presented unprecedented challenges to global healthcare systems. Declared a pandemic by the World Health Organization on 11 March 2020, COVID-19 has disrupted routine clinical care and created specific concerns for patients receiving systemic immunotherapy, particularly for inflammatory skin disorders. This review synthesizes current evidence on immunomodulatory therapies in the context of SARS-CoV-2 infection, focusing on balancing treatment continuation with infection risk, immune response alterations, and the risk of flare-ups. Furthermore, we critically evaluate therapeutic strategies—including corticosteroids, Remdesivir, oxygen therapy—and address the limitations of unproven interventions such as hydroxychloroquine, ivermectin, and convalescent plasma. The review also discusses public health strategies, including early home-based management, vaccination, testing, and social behavior interventions, emphasizing their role in mitigating healthcare system overload. Based on evolving evidence, we provide practical recommendations for clinicians managing immunocompromised patients during the ongoing and future pandemics.